(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article presents the results of a comparative evaluation of the duration of post-vaccination immunity induced by inactivated Newcastle disease vaccines based on different virus strains. The La Sota strain was found to induce a short-term immune response, while the H strain elicited longer-lasting protection. The longest duration of humoral immunity (up to 20–22 weeks) was observed with the vaccine based on the PMV-1/chicken/Astana/49/98 strain. The use of Montanide ISA 70 and ISA 78 oil adjuvants enhanced and prolonged the immune response. These data confirm the effectiveness of using local virus isolates and modern adjuvants in the development of vaccines with a long-lasting protective effect against Newcastle disease.